The Process of Forming Sensation-Seeking Behavior in Online Slot Gambling Players - Faischa Nadiyah Fiyanda; RR Setyawati; Herdian; Suwarti (Indigenous: Jurnal Ilmiah Psikologi, 2024)
Online slot gambling is a massive case, especially in Indonesia. In this context, individuals tend to develop repetitive habits in using the internet, which can lead to increased frequency of use and potentially trigger addictive behavior. Therefore, the rise of addiction cases in gambling behavior ultimately led to a sensation-seeking behavior in playing gambling. The purpose of this study is to determine sensation seeking behavior in online slot gambling players. This research uses a qualitative approach with a case study method, specifically a holistic single case study conducted by 5 primary and 3 secondary participants. Semi-structured interviews and observations were used as data collection techniques. The data analysis technique uses thematic analysis using NVivo 14 Plus software. The results of this study are that the research participants showed this tendency through the statement that playing online slot gambling provides fun, curiosity, and adrenaline that spurs them to continue to seek these sensations. This research highlights that thrill, adventure-seeking, and disinhibition in online slot gambling players are the most significant aspects in the sensation-seeking behavior of gambling players. It also found components namely moral disengagement, pleasure and gratification, and risk-taking behavior. This research highlights the formation of sensation-seeking behavior in online slot gambling players, as well as its implications for online gambling behavior. This research is expected to be a reference for overcoming online gambling addiction and the dynamics of sensation-seeking in addictive behavior.